2020
DOI: 10.1111/ene.14295
|View full text |Cite|
|
Sign up to set email alerts
|

Using machine learning to predict stroke‐associated pneumonia in Chinese acute ischaemic stroke patients

Abstract: Background and purpose Stroke‐associated pneumonia (SAP) is a common, severe but preventable complication after acute ischaemic stroke (AIS). Early identification of patients at high risk of SAP is especially necessary. However, previous prediction models have not been widely used in clinical practice. Thus, we aimed to develop a model to predict SAP in Chinese AIS patients using machine learning (ML) methods. Methods Acute ischaemic stroke patients were prospectively collected at the National Advanced Stroke … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…This model assesses risk factors, including age, atrial fibrillation, dysphagia, sex, and previous stroke severity. In a total of 3,160 Chinese AIS patients, Li et al ( 16 ) used machine learning methods to develop a model with high sensitivity and specificity to predict SAP. Interestingly, a study found that reduced vitamin D was a potential risk factor of SAP ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…This model assesses risk factors, including age, atrial fibrillation, dysphagia, sex, and previous stroke severity. In a total of 3,160 Chinese AIS patients, Li et al ( 16 ) used machine learning methods to develop a model with high sensitivity and specificity to predict SAP. Interestingly, a study found that reduced vitamin D was a potential risk factor of SAP ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…SAP not only increases the length of hospital stay and hospital costs [4,5], but is also an important risk factor for poor outcomes after acute stroke [6,7]. Therefore, it is important to nd a scale that is effective in predicting SAP and can help clinicians take early preventative measures to reduce the incidence of SAP [8,9]. Based on the con rmed risk factors for SAP, including an older age, the male sex, dysphagia, preadmission dependency, stroke severity, etc.…”
Section: Introductionmentioning
confidence: 99%
“…ML models are usually constructed based on high volume data recorded in the electronic patient record (EPR) systems and its deep learning ability allows ML models to capture complex, nonlinear relationships, even previously unknown correlations in big data, digging deeper into clinical data [14], and shows promising potential in clinical scenes where large amount of data were collected and integrated every day. Recently, Li and colleagues [15] have developed a model using ML methods to predict stroke-associated pneumonia in Chinese patients with acute ischemic stroke. In addition, ML was used to predict severe pneumonia during posttransplant hospitalization in recipients of a kidney transplant [16].…”
Section: Introductionmentioning
confidence: 99%